Response surfaces for compressive strength of concrete - Cihan, M. Timur; Guner, Abdurrahman; Yuzer, Nabi (ELSEVIER SCI LTD, 2013)
The aim of total quality management (TQM) is to offer satisfactorily high quality products to customers for providing increased productivity and decreased costs. Various methods are used for process improvement, development and optimization. In ready mixed concrete production, the number and the variations of effect parameters can be reduced using response surface methodology. In this study, firstly influence levels of the main and interaction terms of effect variables were determined using 2(7-3) fractional factorial design in order to reduce the number of simultaneously controllable variables. Then, quadratic terms were determined using D-Optimal design, and response surface graphics were plotted. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Compressive strength; Response surface methodology; Fractional factorial design; D-Optimal design; Construction & Building Technology; Engineering; Materials Science